Physical and psychOLOGical functions in Patients WITH THE END-STAGE RENAL DISEASE - Andrea Mahrova; Klara Svagrova; Vaclav Bunc (The Korean Society of Nephrology, 2012)
Understanding the physical and psychological status in patients with the end-stage renal disease (ESRD) on renal dialysis treatment (RDT) is a current issue of high importance due to a rising number of elderly patients. The aims of the study in ESRD patients were: 1) to test physical and psychological functions; 2) to propose suitable physical activities. Group of patients: (M/F,n=34/33, age 67.0±12.7yrs/64.0±13.1yrs). For testing we used Senior Fitness Test Manual, KDQOL-SFTM-questionnaire SF36, WHOQOL-BREF, Importance of quality of the life (QoL) - WHOQOL-100. Results were analysed using descriptive statistics and non-parametric Wilcoxon signed-rank test. In general, both the physical and psychological conditions were severely deteriorated in most components as compared to the non-renal population. Physical fitness was below the normal range of standard values, or to its lower limits, particularly in the tests requiring some degree of muscular strength of the lower limbs and physical efficiency. QoL results showed that in SF36 ESRD patients coincided with the normal range only in the domain of EWB-mental health. The questionnaire WHOQOL-BREF showed that QoL was: significantly lower in ESRD patients than in healthy population only in the domain "physical health". The most important domains of WHOQOL-100 were the domain of "independence" (the ability to take care of everyday needs - 4.5 and the ability to move - 4.3), "environment" (especially items related to the quality of health care - 4.4). The ESRD patients, especially the elderly, should be encouraged to pay attention to increased physical activity levels in order to maintain functional independence and high quality of the life for as long as possible.